2020
DOI: 10.3390/ijerph17145001
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome and Work-Related Stress in Physical and Occupational Therapists Working in Different Types of Hospitals: Which Group Is the Most Vulnerable?

Abstract: Because of the nature of their work, physical and occupational therapists are at high risk of burnout, which is associated with decreased job satisfaction, medical errors, and mental wellbeing in healthcare professionals. To well manage and minimize potential impact of burnout, risk factors should be determined. This study examined burnout and job stress in physical and occupational therapists in various Korean hospital settings. Physical and occupational therapists from several rehabilitation facilities in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 37 publications
1
31
0
12
Order By: Relevance
“…In terms of the gender differences in the relationship between job stress and mental well-being, the study revealed that the negative association of job stress on mental well-being were more consistent among women than men, although some studies have reported inconsistent findings [ 31 ]. This result is in line with previous studies that suggested that there is a higher association in the relationship between job stress and negative mental well-being among women than men [ 25 , 29 , 59 , 60 ]. Several possible reasons may explain these findings.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of the gender differences in the relationship between job stress and mental well-being, the study revealed that the negative association of job stress on mental well-being were more consistent among women than men, although some studies have reported inconsistent findings [ 31 ]. This result is in line with previous studies that suggested that there is a higher association in the relationship between job stress and negative mental well-being among women than men [ 25 , 29 , 59 , 60 ]. Several possible reasons may explain these findings.…”
Section: Discussionsupporting
confidence: 93%
“…Psychological exhaustion among occupational therapists is a critical problem that necessitates counteractive measures because it threatens their psychological well-being and is difficult to reverse. Therefore, it is important to develop preventive measures to reduce the incidence of burnout and its promotional factors in order to prevent individuals from becoming psychologically exhausted [15]. Studies related to burnout among occupational therapists are continuously being reported.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been shown that emotional exhaustion negatively affects the job satisfaction of not only nurses but also that of doctors and medical technicians (Tarcan et al, 2017). Recent studies have found that the risk of developing burnout varies widely among occupational therapists (Bruschini et al, 2018;Derakhshanrad et al, 2019;Escudero-Escudero et al, 2020;Kim et al, 2020;Reis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent international research into occupational therapists' work well-being has mainly focused on negative aspects, for instance, burnout (e.g. Escudero-Escudero et al, 2020;Kim et al, 2020) and workplace fatigue (Brown et al, 2017). However, research in this field should also take into account positive aspects (e.g., job satisfaction) in order to provide a comprehensive description of work well-being (Turner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%